Transpedicular lag screw placement in traumatic cervical spondylolisthesis: Case report and systematic review of the literature. (May 2019) - Bakhsheshian, Joshua; Sizdahkhani, Saman; Ohiorhenuan, Ifije; Buchanan, Ian A.; Strickland, Ben; Pham, Martin H.
Highlights: The optimal approach for stabilization of traumatic spondylolisthesis of the cervical spine is unknown. This report presents a case where C2 pedicle lag-screws were used and reviews the supporting literature. C2 pedicle lag-screws has been shown to be a viable option in the management of traumatic spondylolisthesis of the axis. The supporting evidence for use of C2 pedicle lag screw placement is limited to level IV studies. Abstract: Traumatic spondylolisthesis of C2-C3 is an unstable fracture. Posterior fixation techniques can be employed with intraoperative navigation, however this tool is not available to all spine surgeons. Furthermore, the evidence for posterior surgical stabilization of C2, while adhering to motion preservation principles is currently unknown. The authors describe a patient who had fractures of the pedicle and vertebral body of C2 and C3, which was successfully stabilized with freehand placement of C2 pedicle lag screws and subsequent C2-C5 fixation. Subsequently, a systematic review was performed to evaluate studies that utilized C2 lag screw placement in patients with traumatic spondylolisthesis of the axis (TSA). Eight retrospective case series were identified (N = 63 patients). Five studies evaluated an open posterior cervical approach and 3 investigated a percutaneous approach. Follow-up time ranged from 2 to 48 months and fusion was successful in most cases. No intra-operative complications were reported. On final follow-up, 2 patients had unintentional C2-C3 fusion, and 3 had C2-C3 instability. Three minor complications (urinary tract infection, surgical site hematoma, respiratory infection) were also reported, that resolved with medical management. Freehand placement of C2 pedicle lag screws may be a viable option in select cases. While posterior C2 lag-screw fixation demonstrated successful fusion in most patients with TSA, the supporting evidence is limited to level IV studies.